Prediksi Risiko Kredit Berdasarkan Rasio Likuiditas, Rasio Solvabilitas, dan Kualitas Laba di Perusahaan Pembiayaan yang Terdaftar pada Bursa Efek Indonesia (BEI) - Yushi Ana; Khadijah Khadijah; Ferdila Ferdila; Andi Auliya Ramadhany; Baru Harahap (Lembaga Yasin AlSys, 2026)
Credit risk in financing companies is an important issue influenced by various financial indicators, but studies that specifically integrate liquidity ratios, solvency ratios, and earnings quality in a single predictive model remain limited. This study aims to analyze the effect of liquidity ratios, solvency ratios, and earnings quality on credit risk. This study used a quantitative approach with a causal research design, involving 68 data points from financing companies listed on the Indonesia Stock Exchange for the 2021–2024 period selected through purposive sampling. Data were collected through the documentation method from financial statements and analyzed using multiple linear regression. The results showed that the liquidity ratio had a negative and significant effect on credit risk, the solvency ratio had a positive and significant effect, while earnings quality had no significant effect. Simultaneously, the three variables had a significant effect on credit risk. These findings contribute to the development of risk management theory and expand understanding of the determinants of credit risk in the financing sector. The conclusion of the study emphasizes the importance of liquidity management and debt structure in controlling credit risk. The implications of this study include theoretical and practical contributions for companies and investors, while also opening opportunities for further research by incorporating broader variables.